(untitled) (Journal of Geography and Environmental Management, 2022)
Desertification is a slow and imperceptible crisis. In turn, it undermines the sustainability of the global community. The process of desertification occurs under the influence of various factors in nature. Desertification is a consequence of a number of important processes occurring in arid and semi-arid conditions. Usually, the process of desertification of the territory of Kazakhstan and Central Asia is considered due to the changes in its geological periods.The paper examines the problems of desertification in Kazakhstan and measures to prevent it, because the desert area occupies most of its territory and it is one of the regions prone to desertification in the world. In this research work, we analyzed the main features of Kazakhstan’s arid and semi-arid zones, the spatial distribution of Kazakhstan’s desertification susceptibility, the processes of its formation history, the adverse effects of desertification, and measures to prevent desertification processes in Kazakhstan. The results of the analysis of the above-mentioned contents show that the majority of the territory of Kazakhstan, especially in the southern and western regions with a dense population, has a lot of arid and semi-arid lands, and at the same time, these regions are prone to desertification. As we have seen from the discussion of the negative effects of desertification, desertification and drought in Kazakhstan cause not only environmental, but also economic and social problems. Another thing we noticed is that although measures to prevent desertification in Kazakhstan were well taken during the Soviet Union, since the years of independence, it has not been considered as an important issue. However, the results of the analysis of the materials also show that in the last ten years, a number of international and state-level measures to deal with desertification have been initiated in Kazakhstan. At the same time, one of the actual problems identified in the article is the incomplete implementation of some projects to prevent desertification in Kazakhstan or their stagnation, this phenomenon requires further in-depth research.